2011
DOI: 10.1039/c1md00003a
|View full text |Cite
|
Sign up to set email alerts
|

Progress on lamellarins

Abstract: 5This review covers recent literature on the lamellarins, a family of marine natural products, and related analogs, encompassing synthetic strategies for total synthesis, structure-activity relationships (SAR), and studies on mechanisms of biological action, namely in the context of antitumor activity. It reviews work published

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
44
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(44 citation statements)
references
References 31 publications
0
44
0
Order By: Relevance
“…This approach compares most favourably with all other syntheses of this compound reported to date and surpasses the hitherto most efficient general and restricted protocols (Yadav et al, 2009: [7g] 44 % overall, uses molecular symmetry and has not been extended to other lamellarins; Ruchirawat et al, 2001: [6a, 7b] 27 % overall, general applicability demonstrated). [13] An updated comparison [7h] of syntheses of 1 a can be found in the Supporting Information. Our scalable procedure could be extended without any difficulties to the total synthesis of the 5,6-unsaturated lamellarin h (1 e) as well as its dihydro analogue 1 c in overall yields of 54 (10 steps) and 59 % (9 steps), respectively, and does not involve any expensive reagents or catalysts.…”
mentioning
confidence: 99%
“…This approach compares most favourably with all other syntheses of this compound reported to date and surpasses the hitherto most efficient general and restricted protocols (Yadav et al, 2009: [7g] 44 % overall, uses molecular symmetry and has not been extended to other lamellarins; Ruchirawat et al, 2001: [6a, 7b] 27 % overall, general applicability demonstrated). [13] An updated comparison [7h] of syntheses of 1 a can be found in the Supporting Information. Our scalable procedure could be extended without any difficulties to the total synthesis of the 5,6-unsaturated lamellarin h (1 e) as well as its dihydro analogue 1 c in overall yields of 54 (10 steps) and 59 % (9 steps), respectively, and does not involve any expensive reagents or catalysts.…”
mentioning
confidence: 99%
“…[19,20,21] It is worth noting that the pyrroloA C H T U N G T R E N N U N G [2,1-a]isoquinoline substructure is present in lamellarins, a class of marine natural products with useful biological properties such as antitumor and anti-HIV activities. [22] Taking into consideration that the starting ketones 1 are readily prepared from the corresponding NÀH azoles and bromoketones, this methodology may represent a highly modular approach for the preparation of this class of heterocycles.…”
mentioning
confidence: 99%
“…The current good possibility that cephalostatin/ritterazine alkaloids inhibit cancer cell growth by affecting a novel molecular target(s), the ongoing total synthetic and SAR challenges, the possibility of locating a marine microorganism source actually responsible for their biosynthesis, and clinical development prospects all suggest that the bis steroidal alkaloids field will become increasingly productive and useful. Among the most promising anti-cancer drug candidates derived from marine invertebrates is the family of lamellarins [37][38][39][40][41]. The lamellarins form a group of more than 50 highly condensed DOPA-derived pyrrole alkaloids that have attracted researchers' interest due to both their structural originality and significant biological properties.…”
Section: Bis-steroidal Pyrazines: Ritterazines and Cephalostatins Pomentioning
confidence: 99%
“…This DNA interaction, although relatively weak, provides the necessary anchorage for stabilization of the enzyme-DNA complex. Inhibition of topoisomerase I by lamellarin D has been demonstrated by a variety of approaches, both in vitro (using recombinant enzymes and model DNA substrates) and in a cellular context, using immunoblot assays to detect the drug-stabilized topoisomerase I-DNA complexes in cells [40,41].…”
Section: Bis-steroidal Pyrazines: Ritterazines and Cephalostatins Pomentioning
confidence: 99%
See 1 more Smart Citation